2005
DOI: 10.1182/blood-2003-04-1319
|View full text |Cite
|
Sign up to set email alerts
|

WAVE/Scars in platelets

Abstract: Using specific antibodies against isoforms of WAVE (WASP [Wiskott-Aldrich syndrome protein] family Verprolinhomologous protein, also called Scar), we demonstrated that human platelets express all 3 isoforms. With the use of an in vitro pull-down technique, the src homology 3 (SH3) domain of insulin receptor substrate p53 (IRSp53) precipitated WAVE2 from platelet lysates more efficiently than did profilin I. The opposite was true for WAVE1, and neither precipitated WAVE3, suggesting that WAVE isoforms have diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Next, we addressed whether RECK can influence the aminopeptidase activity of CD13. Introduction of exogenous RECK reduced the cell surface aminopeptidase activity to a level comparable with that in cells that were treated with a non-cytotoxic concentration of bestatin, a specific aminopeptidase inhibitor (31) (Fig. 3E).…”
Section: Reck Physically Interacts With Cd13 and Competitively Inhibimentioning
confidence: 79%
See 1 more Smart Citation
“…Next, we addressed whether RECK can influence the aminopeptidase activity of CD13. Introduction of exogenous RECK reduced the cell surface aminopeptidase activity to a level comparable with that in cells that were treated with a non-cytotoxic concentration of bestatin, a specific aminopeptidase inhibitor (31) (Fig. 3E).…”
Section: Reck Physically Interacts With Cd13 and Competitively Inhibimentioning
confidence: 79%
“…Mass Spectrometry-Mass spectrometric identification of proteins was performed by using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to the results shown here for CX3CL1, WAVE2 and WASP are known downstream effectors of Rac and Cdc42 that are required for actin remodeling and chemotaxis in macrophages in response to CSF-1 (20,24,30,32). WAVE2 does not bind directly to Rac and IRSp53 was reported to be an important candidate linking WAVE2 to Rac1 (61,62). Consistent with IRSp53 in mediating the interaction between Rac and WAVE2, WAVE2 was present in a complex with Rac1 and IRSp53 in response to CX3CL1 and disruption of this interaction using a dominant-negative form of IRSp53-inhibited membrane protrusions in response CX3CL1.…”
Section: Discussionmentioning
confidence: 93%
“…Although WAVE2 has a well-documented function in cell migration, regulation of WAVE2 has proven to be very complicated as Rac1 does not bind directly to WAVE2, as is the case between Cdc42 and WASP/N-WASP proteins. Based mostly on in vitro studies, IRSp53 was reported to be an important candidate linking WAVE2 to Rac1 (Miki and Takenawa, 2002;Miki et al, 2000;Oda et al, 2005;Suetsugu et al, 2006a). However, whether IRSp53 functions as an essential intermediate between Rac1 and WAVE2 in vivo was not established.…”
Section: Discussionmentioning
confidence: 99%